Carbon nanotubes-based adsorbents: Properties, functionalization, interaction mechanisms, and applications in water purification. (June 2022) - Sajid, Muhammad; Asif, Mohammad; Baig, Nadeem; Kabeer, Muhamed; Ihsanullah, Ihsanullah; Mohammad, Abdul Wahab
Abstract: Carbon nanotubes-based adsorbents have been extensively used in the adsorption of inorganic and organic pollutants from water and wastewater. They demonstrate excellent adsorption properties due to their high specific surface area, exceptional porosities, hollow and layered structures, numerous internal and external adsorption sites, π-conjugative structure, and ease of chemical activation and functionalization. A wide range of mechanical, physical, and chemical approaches have been used for the modification or functionalization of carbon nanotubes to enhance their adsorptive properties in general or to make them selective toward certain classes of pollutants. Depending on the adsorption conditions and the functionalization involved, carbon nanotubes-based adsorbents can interact with inorganic contaminants through different mechanisms such as surface complexation, electrostatic interaction, ion exchange, physical adsorption, and precipitation. In the case of organic pollutants, besides physical adsorption, π-π and electrostatic interactions play a major role in adsorption. In some cases, chemical bonding between organics and carbon nanotubes has also been reported as a mechanism of interaction. This review summarizes the properties, functionalization, and mechanisms involved in carbon nanotubes-based adsorption of pollutants from aqueous media. An insightful overview of the critical parameters that should be considered while using carbon nanotubes-based adsorbents for water purification is also provided. In the end, some challenges associated with carbon nanotubes-based adsorbents are presented, along with the potential solutions. This review will be useful for the researchers working in the field of water treatment. Graphical abstract: Unlabelled Image Highlights: CNTs are excellent adsorbent materials due to their unique structural features. The functionalization of CNTs might enhance their adsorption selectivity and performance. CNTs based adsorbents can interact with pollutants in aqueous media through various mechanisms. The challenges related to large-scale applications of CNT-based adsorbents await solutions.